Feasibility of utilizing Indian almond (Terminalia catappa L.) for value addition - Manjusha P M (Department of Home Science, College of Agriculture, 2010)
The study entitled ‘Feasibility of Utilizing Indian Almond (Terminalia catappa L.) for value addition’ was conducted at College of Agriculture, Vellayani. The major objective of the study was to assess the quality characteristics of Indian almond kernel and to find out the feasibility of utilizing the kernel for product development.